Synthesis of 1-Amidoalkyl-2-Naphthols by Two-Component Friedel-Crafts Reaction - Liu, Li-Ping; Yu, Liang-Min; Zhang, Zhi-Ming; Yan, Xue-Feng (Asian Journal of Chemistry, 2013)
A one-pot two-component Friedel-Crafts reaction of 1-amidoalkyl-2-naphthols by the condensation of 2-naphthol with various N-methyl hydrocarbon unsaturated amides in presence of the concentrated sulphuric acid as catalyst and anhydrous ethyl alcohol as solvent to form the corresponding amidoalkyl naphthols is described. This procedure offers advantages such as eco-friendly, shorter reaction times, simple work-up, excellent yields and recovery and reusability of the catalyst. The spectroscopic properties are assessed for their effectiveness and the fluorescent intensity sequence of three compounds in two different solvents follows the sequence: 1-N-methacrylamide-2-naphthol > 1-N-methy phthalimide-2-naphthol > 1-N-methy phthalimide-2-naphthol.